Influence of Diabetes Mellitus on Dental Condition and Periodontal Status - H. Poskerová; P. Bořilová Linhartová; M. Cvanová; L. Izakovičová Hollá (Czech Dental Chamber, 2018)
Introduction, aim: Diabetes mellitus (DM) and periodontitis are chronic inflammatory diseases with high prevalence. Both conditions possess some common traits and can mutually affect each other. The aim of the study was to investigate the state of teeth and periodontium in Czech diabetic patients and contribute to the identification of genetic risk factors of both diseases. Methods: We examined and mutually compared three groups of subjects: type 1 diabetic patients (T1DM), type 2 diabetic patients (T2DM) and subjects without diabetes mellitus (controls). The subjects included in the study underwent clinical, radiological and further we focused on the analysis of microbiological composition of subgingival plaque. Evaluation of results was performed by statistical software IBM SPSS Statistics 23. Results: The study comprised a total of 141 subjects (32 with T1DM, 51 with T2DM, 58 controls), aged 35-65 years, examined during 2010-2015. We found that the state of teeth and periodontium in diabetic (mainly T2DM) patients was worse than in subjects without diabetes. This finding was confirmed for plaque index and gingival index, number of extracted teeth, the presence of teeth replacement and other parameters evaluating the presence and severity of periodontitis. The differences in the representation of periodontal pathogens and their quantity among the groups were minimal. Patients with T2DM and diabetic nephropathy had worse state of the periodontium; this finding was not proven in patients with insufficiently controlled diabetes or the disease duration. Conclusion: In diabetic patients, a more frequent occurrence of inflammatory periodontal diseases and other diseases of the oral cavity is expected. Based on clinical examination and anamnestic data, the dentist can presume DM, early treatment of periodontal disease contributes to improved general health of the patient.